2018
DOI: 10.1007/s00294-018-0849-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the epigenetic inheritance of stress response in single cells

Abstract: Cells have evolved to dynamically respond to different types of environmental and physiological stress conditions. The information about a previous stress stimulus experience by a mother cell can be passed to its descendants, allowing them to better adapt to and survive in new environments. In recent years, live-cell imaging combined with cell-lineage tracking approaches has elucidated many important principles that guide stress inheritance at the single-cell and population level. In this review, we summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…For instance, carbonylated proteins can form aggregates that are resistant to proteasome digestion [33, 34], and ERCs are self-replicating, suggesting that their effective repair rate – accounting for such self-replication – is probably also low [15, 35]. Finally, for asymmetric partitioning of damage in particular, it has been reported that some organisms like S. pombe and E. coli only exhibit this behavior during high levels of external stress [14, 17, 32, 36], suggesting that they may actually have evolved mechanisms to activate or inactivate damage partitioning depending on the region of parameter space they are in, just like other stress response mechanisms that are only activated in the presence of stress and can be epigenetically inherited by daughter cells [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, carbonylated proteins can form aggregates that are resistant to proteasome digestion [33, 34], and ERCs are self-replicating, suggesting that their effective repair rate – accounting for such self-replication – is probably also low [15, 35]. Finally, for asymmetric partitioning of damage in particular, it has been reported that some organisms like S. pombe and E. coli only exhibit this behavior during high levels of external stress [14, 17, 32, 36], suggesting that they may actually have evolved mechanisms to activate or inactivate damage partitioning depending on the region of parameter space they are in, just like other stress response mechanisms that are only activated in the presence of stress and can be epigenetically inherited by daughter cells [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…In specific cases, survival is improved when yeast cells “remember” a previous stressful experience, and are capable not only of a more rapid reactivation of the appropriate transcriptional stress response, but also of transmitting this response to their descendants. Here, we focus on examples of epigenetic transcriptional memory implicating chromatin modifications, although alternative mechanisms have been reported [4].…”
Section: Histone Methylation and Transcriptional Memory Of Stressmentioning
confidence: 99%
“…For instance, carbonylated proteins can form aggregates that are resistant to proteasome digestion [33,34], and ERCs are self-replicating, suggesting that their effective repair rate – accounting for such self-replication – is probably also low [15,35]. Finally, for asymmetric partitioning of damage in particular, it has been reported that some organisms like S. pombe and E. coli only exhibit this behavior during high levels of external stress [14,18,32,36], suggesting that they may actually have evolved mechanisms to activate or inactivate damage partitioning depending on the region of parameter space they are in, just like other stress response mechanisms that are only activated in the presence of stress and can be epigenetically inherited by daughter cells [37,38].…”
Section: Discussionmentioning
confidence: 99%